2016
DOI: 10.1097/md.0000000000005776
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting venous thromboembolism after spine surgery

Abstract: Background:A meta-analysis was performed to explore predicted factors of venous thromboembolism (VTE) after surgery in the treatment for spine degeneration diseases.Summary of background data:Many scholars have focused on VTE after spine surgery, but as for the risk factors of VTE have not reached a consensus.Methods:An extensive search of literature, “spine or spinal,” “degeneration,” “after surgery or postoperation,” and “venous thromboembolism” as key words, was performed in PubMed/MEDLINE, Embase, the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…74,75 However, other complications including renal failure and myocardial infarction do not have well-defined relationships with operative duration; results are inconsistent across studies and vary across surgical specialties. 76 Thus, it is possible that pooling of all complications across all surgical specialties diluted the effect estimates in our study.…”
Section: Discussionmentioning
confidence: 89%
“…74,75 However, other complications including renal failure and myocardial infarction do not have well-defined relationships with operative duration; results are inconsistent across studies and vary across surgical specialties. 76 Thus, it is possible that pooling of all complications across all surgical specialties diluted the effect estimates in our study.…”
Section: Discussionmentioning
confidence: 89%
“…The overall incidence of VTE was 0.35%, which was much lower than in a previous meta-analysis. [ 40 ] In addition, it was found that the incidence of VTE in Asian patients was significantly higher than that in occidental patients, which indicated that Asian patients were more likely to suffer from VTE after spine surgery; the reason for this remains to be investigated by further research. Our study indicated that elderly patients were more likely to develop VTE, which was in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis by Piper et al revealed 13 factors associated with VTE: nine preoperative factors (dependent functional status, paraplegia, quadriplegia, disseminated cancer, inpatient status, hypertension, history of transient ischemic attack, sepsis, and African American race); three operative factors (surgery duration >4 hours, emergency presentation, and American Society of Anesthesiologists Class III‐V); and one postoperative factor, sepsis . Another meta‐analysis describing VTE incidence showed higher incidence of VTE after spine surgery when wearing elastic stockings, undergoing lumbar surgery, having a history of hypertension and diabetes, being of Asian descent, or having ambulatory impairments prior to surgery . The commonalities between these two studies are the preoperative immobility status and hypertension as predictive factors.…”
Section: Discussionmentioning
confidence: 99%